Theorising Transformative Learning : The Power of Autoethnographic Narratives in Education. - Pandey, Kashi Raj. (Boston : BRILL, 2021)
Educational reality is weaved within stories, poems, and dialogues, as the author demonstrates his becoming of a transformative educator. Transformative learning is important for teachers to think about their practices, change their thinking, and share the stories of their experience for learners' empowerment. This is an autoethnographic account of the author's experience as a transformative and transforming educator that unfolds the ways he has used ethical dilemma story pedagogy to explore interpretative and creative spaces for transformative learning, both personally and with a group of trainee teachers who take the responsibility to facilitate students' learning into a purposeful path. The ethical dilemma story pedagogy provides relatable scenarios to challenge and unsettle learners' thought processes leading to acknowledgment of multiple viewpoints. Theorising Transformative Learning serves to help educators utilise the sociocultural contexts connected to students' lives and experiences.
2 Resisting 'Banking' Approaches to Pedagogy -- 3 Fostering Critical Awareness -- 4 Rethinking Culture and Education -- 5 Honouring Home Language in the Context of English -- 6 All Our Students Speak in English -- 7 Promoting Emancipatory Interests in EFL Classrooms -- 8 Trailing towards the Transformative Path -- 9 Learning the Notes -- 10 Life Moves On -- 11 The Ethical Dilemma Story Method -- 12 The Contextual Salience of Ethical Dilemma Stories -- 13 The Dilemma of Life and How We Live -- 14 The Dilemma of Leaving Home -- 15 Ethical Components in Classroom Teaching -- 16 A Transformative Touch I Often Imagine -- 17 A Teacher's Guide to Ethical Dilemma Story Pedagogy -- 18 The Use of Ethical Dilemma Stories in Transformative Pedagogy -- 19 My Fieldwork Implications of Ethical Dilemma Story Pedagogy -- 4 Mapping the Nature of Ethical Dilemma Stories and Transformative Learning -- 1 Personal Reflection as a Transformative Learner -- 2 A Transformative Pedagogy through Autoethnographic Narratives -- 3 A Penultimate Breather: Some Reflections on My Journey into a Transformative Pedagogy -- Coda -- References -- Index.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Pandey, Kashi Raj; Transformative learning; Critical pedagogy; Ethnology -- Authorship; Ethnology -- Research; Ethnology -- Methodology; Apprentissage transformateur; Pédagogie critique; Ethnologie -- Recherche; Ethnologie -- Méthodologie.; Critical pedagogy; Ethnology -- Authorship; Ethnology -- Methodology; Ethnology -- Research; Transformative learning; Electronic book